Pengaruh Promosi Media Sosial dan E-Wom terhadap Keputusan Berkunjung Wisatawan di Dermaga Rindu Kabupaten Bangkalan - Aulia Oktaviani; A. Yahya Surya Winata (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of social media promotions and eWOM (electronic worth of mouth) on tourists' visiting decisions at Dermana Rindu, Bangkalan Regency. This research was conducted using quantitative methods, using descriptive analysis and multiple linear regression analysis. The population in this study were all tourists who had visited the Rindu Jetty tour in Bangkalan Regency. The sampling technique in this study used probability sampling, and analysis using SPSS IBM 26 software. Based on the results of the descriptive analysis, it shows that the decision to visit is in the high category, so promotion through social media is in the high category as well as e-wom is in the good category. Based on the results of multiple linear regression analysis that promotion through social media and electronic word of mouth partially has a positive effect on the decision to visit the Pier Rindu tour, Bangkalan Regency. Furthermore, promotions through social media and electronic word of mouth simultaneously have a positive effect on the decision to visit the Rindu Pier tour, Bangkalan Regency.